F. M. Dostoevsky in literary and critical works of Andrei Bely: the dialectic of the self-knowing consciousness - Гармаш, Людмила Викторовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
Andrei Bely’s reception of philosophical views and artistic discoveries of F. M. Dostoevsky has analyzed. The dynamics of changes in the assessment of a representative of the younger generation of symbolists of the personality and creative heritage of F. M. Dostoevsky in order to highlight those stages that correspond to well-known Hegelian dialectical triad – thesis, antithesis, synthesis has considered. Three periods, during which Bely’s assessment of the work of the great classical writer had been undergone significant transformation: the apologetic (admiration for the idol in his teenage years), critical (sharp rejection of the personality and creativity of the writer, which was formed in the minds of Bely’s contemporaries) and synthetic (acceptance of the artistic world of Dostoevsky in its entirety and completeness) have marked.